STUDI EVALUASI INSTALASI PENGOLAHAN AIR BERSIH UNTUK KEBUTUHAN DOMESTIK DAN NON DOMESTIK (STUDI KASUS PERUSAHAAN TEKSTIL BAWEN KABUPATEN SEMARANG) - Hardyanti, Nurandani; Fitri, Nurmeta Diana (Universitas Diponegoro, 2006)
Water was the fundamental needs for industrial in every production process and all the activities. Apac Inti Corpora company was the textile industrial with production process are spinning and weaving. It usually required water with high quality such as lowest pH and hardness. They needed high quality water by water treatment plant. They treated ground water that contained manganese and iron to fulfill domestic needs by aerasi and filtrasi with filter sand. They treated water from Bade river and Sarana Tirta Ungaran to fulfill non domestic needs. Water from Bade river contained highest colour and turbidity and processed with screening, coagulation, flokulalation, sedimentation and filtration. To eliminate content of hardness, these water continued to treat by softener unit. Softener unit will degrade kesadahan less than 5 ppm CaCO 3 . Quality of treated water has been fulfilled Permenkes RI No.907/MENKES/SK/VII/2002, except colour content from Bade river.